Analysis of 4G LTE Indoor Networks Performance with Networks in the Engineering Faculty G5 Building Universitas Muhammadiyah Yogyakarta - Widyasmoro Widyasmoro; Ramadoni Syahputra; Kunnu Purwanto; Dedy Prasetiyo; Yessi Jusman (Journal of Electrical Technology UMY, 2019)
Analysis of the performance of the LTE network with WiFi networks was carried out in the G5 building of the Faculty of Engineering, University of Muhammadiyah Yogyakarta, which is the building of the Faculty of Engineering Laboratory. This research was conducted by comparing the LTE network with indoor or indoor WiFi networks, measuring these two networks using the Network Analyzer and Wifi Analyzer application to obtain information on signal quality data based on KPI and TIPHON standardization, which shows RSRP, RSRQ, and Throughput values through measurement using the Network Analyzer and Wifi Analyzer application. From the results of research that has been done shows that the G5 building has a WiFi internet network that is superior to the LTE internet network. The overall condition of the Wifi network is in very good condition and is stable for each floor. While the LTE network even though it has increased conditions on the second floor but overall is in a bad condition to normal. The LTE network has an RSRP value with an average of -143 dBm, while a WiFi network with an average of -90 dBm. Then the LTE network has an RSRQ value with an average of -13 dBm, while the Wifi network with an average of -15 dBm. For LTE network throughput it has an average max. ping by 50.9 ms and min. ping is 864.5 ms, while WiFi networks have max average. ping by 24.3 ms and min. ping of 144.5 ms. From the results of these data show that the G5 Building has a good WiFi network and is superior to the LTE network.